Vehicle Thermal Management Systems proceedings : VTMS 10, Heritage Motor Centre, Gaydon, Warwickshire, U.K., 15-19 May 2011 (Woodhead Pub., 2011)
This book contains the papers presented at the IMechE and SAE International, Vehicle Thermal Management Systems Conference (VTMS10), held at the Heritage Motor Centre, Gaydon, Warwickshire, 15-19th May 2011. VTMS10 is an international conference organised by the Automobile Division and the Combustion Engines and Fuels Group of the IMechE and SAE International. The event is aimed at anyone involved with vehicle heat transfer, members of the OEM, tier one suppliers, component and software suppliers, consultants, and academics interested in all areas of thermal energy management in vehicles. This vibrant conference, the tenth VTMS, addresses the latest analytical and development tools and techniques, with sessions on: alternative powertrain, emissions, engines, heat exchange/manufacture, heating, A/C, comfort, underhood, and external/internal component flows. It covers the latest in research and technological advances in the field of heat transfer, energy management, comfort and the efficient management of all thermal systems within the vehicle.